Development Of Interactive Multimedia For Learning Computer Hardware Maintenance Vocational High School - Hermanus Herawan; Aloysius Mering; Herry Sujaini (STKIP Singkawang, 2022)
The aim of this reasearch was to develop interactive multimedia for learning computer hardware maintenance in Vocational High Schools. To achieve the objectives of this study, the Research and Development (R&D) method of the ADDIE development model was used. The ADDIE development model in research begins through the stages (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. This research was conducted Vocational High School Negeri 6 Pontianak at class X with 27 students participating and three validators, design experts, material experts, and media experts. Data from the instrument and attitude scale were analyzed using qualitative and quantitative analysis. Relatively, from the results of data analysis (in the range of values 1-5) the multimedia design was declared